EARLY CHILDHOOD EDUCATIONAL GAMES BASED ON AL-ISLAM MUHAMMADIYAH - Sari, Mawar; Paradiba, Elza; Almira Sagala, Safina; Auralia Cut, Tazkiah (International Journal of Students Education, 2023)
Early childhood education has an important role in forming the basis of children's character and personality in the context of Muhammadiyah Islam. Education must combine religious values with enjoyable learning. The aim of this research is to develop educational games that are in accordance with Muhammadiyah Islamic principles for young children. These educational games are designed with the aim of teaching Islamic values interactively, encouraging children's creativity and cognitive development, and helping them understand and internalize Islamic teachings in everyday life. One example of a game proposed in this research is Composing the Words of the Creed, where children are asked to compose the words of the creed with pieces of letters provided. The results of the analysis show that this game is effective in teaching religious values to young children. , while promoting their active involvement in the learning process. This game also contributes to children's cognitive development, especially in the aspects of thinking skills and understanding the meaning of Islamic teachings. Thus, this research underlines the importance of a play approach in early childhood education that is based on Muhammadiyah Islam. Games such as Composing the Words of the Creed can be an effective tool in developing children's understanding of religion and character in the Muhammadiyah Islamic education environment.